Pengaruh Tingkat Bagi Hasil dan Promosi Terhadap Minat Nasabah Deposito Barokah: Pengaruh Tingkat Bagi Hasil dan Promosi Terhadap Minat Nasabah Deposito Barokah - Faruk Faruk (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2021)
Islamic banking is an Islamic banking financial institution that has an important role in the economic development of a country. The most important banking activity is to raise funds from the wider community by offering a variety of products and facilities to be provided to prospective customers and one of The highest collection of funds, namely DPK (Third Party Funds) is largely dominated by deposit products. Many factors affect the rapid growth of deposits one of which is the level of profit sharing and promotion carried out by Islamic bank financial institutions for customers. This study examines the effect of the level of profit sharing and promotion on customer interests. The purpose of this study was to determine the factors of the level of profit sharing and promotion affect customer interest. The population used in this study is the barokah deposit customers at the East Java KCP SyariahWiyung Bank in Surabaya. The samples used in this study were 75 customers. The online questionnaire was distributed to barokah deposit customers containing the profit sharing, promotion and customer interest factors. In analyzing the data of this study using quantitative methods that are descriptive statistics with a Likert scale measurement.Data processing in this study uses multiple linear regression analysis. The method used in this study is random sampling, namely simple random sampling. Data collection techniques were processed using SPSS software version 21. The results of this study indicate the variable level of results with t-test values ​​obtained sig 0.00<0.05 partially significant effect on customer interest, promotion variables with t-test values ​​obtained sig 0.00<0.05 partially affect customer interest. The results of this study indicate the two variables, namely the level of profit sharing and promotion with a value (F-count) 87.208>(F-table) 3.12 simultaneously a significant effect on customer interest. 05 partially influences customer interest.